Peripheral corneal ulcers in association with rheumatic diseases - E.A. Drozdova (РМЖ "Клиническая офтальмология")
E.A. Drozdova South-Ural State Medical University, Chelyabinsk, Russian Federation Background: peripheral ulcerative keratitis (PUK) is a polyetiological disease. The pathogenesis of PUK is attributed to a combination of factors, including the anatomy of the peripheral cornea, the activation of autoimmune reactions, and the corneal destruction caused by autoan-tibodies and matrix metalloproteinases. Aim: to describe the clinical symptoms of PUK, its association with rheumatic diseases (RD), its course, and the efficacy of treatment options. Patients and Methods: а total of 32 patients (9 men and 23 women, mean age 59.3±9.4 years) with PUK associated with RD were under surveillance. The diagnosis was established based on the results of eye examinations, tear production test, and multidisciplinary examination. Treatment was performed in an outpatient or inpatient setting based on the severity of corneal lesions. Results: the most common association between PUK and RD was established with rheumatoid arthritis (56.2%). Clinical hallmarks of PUK included mild infiltration and perifocal corneal edema, accompanied by the appearance of an oval or sickle-shaped epithelial and stromal defect 2–4 mm from the limbus. Additionally, rapid corneal lysis and perforation (18.7%) and association with perilimbal vasculitis and scleritis (31.2%) were observed. Bilateral corneal lesions were observed in 56.2%. Tear production, as measured by Schirmer's test, was 6±2 mm, while tear film stability was 2±1 mm. Conservative management was found to be effective in 59.4% (outpatient treatment in 40.6% and inpatient treatment in 18.7%). Surgical interventions were performed for emergent indications, including tectonic keratoplasty (21.9%) and deep anterior lamellar keratoplasty (15.6%). Conclusion: PUK represents a severe clinical manifestation of visual disorders in RD. Treatment for PUK involves local and systemic steroids in the acute period, basic immunosup-pressive therapy, and, when necessary, keratoplasty. Systemic rheumatological therapy, regular use of tear substitutes and reparative preparations are prescribed to prevent recurrences. Keywords: keratitis, corneal ulcer, limbus, autoimmune diseases, rheumatoid arthritis, keratoplasty. For citation: Drozdova E.A. Peripheral corneal ulcers in association with rheumatic diseases. Russian Journal of Clinical Ophthalmology. 2024;24(2):88–93 (in Russ.). DOI: 10.32364/2311-7729-2024-24-2-8.